S-52-5: MEASURING DRUG LEVELS USING A DRIED BLOOD SPOT COMBINED WITH PERSONALIZED FEEDBACK TO IMPROVE RESISTANT HYPERTENSION: A RANDOMIZED CONTROLLED TRIAL. (January 2023) - Peeters, Laura EJ; Kappers, Mariette HW; Hesselink, Dennis A; Gelder, Teun van; Koch, Birgit CP; Versmissen, Jorie
Abstract : Introduction: Identification of non-adherence to antihypertensive drugs is crucial to improve resistant hypertension (RH). For this therapeutic drug monitoring is the most reliable method. Objectives: The primary objective of this study is to determine whether drug levels measured with a dried blood spot (DBS) method combined with personalized feedback leads to a decrease in prevalence of RH after 12 months due to an increase in adherence. Design and method: This is a multi-center single-blinded randomized controlled trial (RHYME-RCT, NL6736). Eligible patients based on previous blood pressure readings underwent DBS sampling and a 24-hour ambulatory blood pressure measurement (ABPM) simultaneously. Patients with a daytime systolic blood pressure (SBP) > 135 and/or diastolic blood pressure (DBP) > 85 mmHg were randomized to a standard treatment (control) arm or intervention arm. The intervention was performed by the treating physician and included information on drug levels and a personalized feedback conversation based on a feedback tool. The follow-up period was one year and included visits at 3, 6 and 12 (T = 12) months inclusion. At each visit an 24h-ABPM and DBS were performed. Results: A total of 141 patients were measured at baseline, of which 100 patients had blood pressures > 135/85 mmHg and were randomized to the intervention (n = 49) or control arm (n = 51). The adherence rate in the excluded population (n = 41) was 78.0%. The randomized patients had a mean age of 59.4 ± 11 years and were predominantly male (70.0%). The prevalence of RH decreased from 100% in both arms to 73.2% at T = 12 in the intervention arm (p = 0.002, n = 37) and 59.1% at T = 12 in the control arm (p < 0.001, n = 41). Adherence rates improved from 67.3% to 92.1% in the intervention arm (p = 0.021) and 68.6% to 71.4% in the control arm (p = 1.000). This increase in adherence was significantly higher in the intervention arm compared to the control arm (p = 0.018). No statistically significant difference was found after 12 months between the two arms in the degree of RH (p = 0.171), SBP (p = 0.297) or DBP (p = 0.655). Conclusions: Measuring blood pressure and drug levels led to a decrease in the prevalence of RH in both arms and improved non-adherence in the intervention arm. However, the improvements in adherence did not lead to a lower blood pressure and degree of having RH. The fact that one third was excluded at baseline because of normotension suggests that participation in a study already leads to improvement of adherence and thus blood pressure control.